Digital Marketing as a Marketing Communication Strategy - A Rizaldi; F Margareta; K Simehate; S N Hikmah; C N Albar; A A Rafdhi (Universitas Komputer Indonesia, 2021)
Digital marketing is a strategy that is quite impactful to increase the number of consumers in the organic fertilizer business sector in an era like today. The purpose of this research is to analyze the marketing strategy of organic fertilizers and the increase in the number of consumers. The research method used was escriptive methods, namely data collection and questionnaires. Methods of data collection carried out by observation, interviews and literature study. The questionnaire was used in analyzing consumers who use organic fertilizers on chilies. The results of this research show that digital marketing as marketing communication is useful in increasing selling power and promotion. This study discusses the use of digital marketing in marketing communications and whether consumers prefer organic fertilizers or not.